2015
DOI: 10.1007/s10597-015-9855-7
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Social Environment and Patterns of Depressive Symptoms Among Patients with Type 2 Diabetes Mellitus

Abstract: This study sought to examine whether neighborhood social environment was related to patterns of depressive symptoms among primary care patients with type 2 diabetes mellitus (DM). Neighborhood social environment was assessed in 179 patients with type 2 DM. Individual patient residential data at baseline was geo-coded at the tract level and was merged with measures of neighborhood social environment. Depressive symptoms at baseline and at 12-week follow up were assessed using the nine-item Patient Health Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Additionally, living in a neighborhood with limited access to healthy food and safe places to exercise can be a significant barrier for diabetes self-care and poorer glycemic control ( 14 , 54 ). O’Donnell et al suggested that patients living in a neighborhood with high social influence, high residential stability, and high neighborhood advantage are much less likely to experience depression ( 55 ).…”
Section: Neighborhood Environmentmentioning
confidence: 99%
“…Additionally, living in a neighborhood with limited access to healthy food and safe places to exercise can be a significant barrier for diabetes self-care and poorer glycemic control ( 14 , 54 ). O’Donnell et al suggested that patients living in a neighborhood with high social influence, high residential stability, and high neighborhood advantage are much less likely to experience depression ( 55 ).…”
Section: Neighborhood Environmentmentioning
confidence: 99%
“…With regards to the domain of non-diabetes medical related variables, chronic kidney disease (n = 6, 4.1%) [10,26,56,65,68,132], hypertension (n = 5, 3.4%) [71,102,149,150], and cardiovascular disease related (n = 3, 2.0%) [50,51,102]. Pertaining to the domain of psychiatric / psychological related variables, depression/anxiety related (n = 9, 6.1%) [21,27,29,35,42,46,[154][155][156] and other psychiatric disorders/symptoms related (n = 5, 3.4%) [22,35,42,62,131] variables were most commonly employed. Lastly for the health systems related domain, types of healthcare utilization (n = 2, 1.4%) [160,161] and type/specialty of care providers (n = 2, 1.4%) [64,77] related variables were most frequently used.…”
Section: Segmentation Variables Usedmentioning
confidence: 99%